The “apostles of terror”: South Africa, the East African campaign, and the Battle of El Wak (Historia, 2021)
Shortly after the outbreak of the Second World War, the Union Defence Force (UDF) had to undergo a rapid transformation from an ageing defence force to one that could project offensive power across Africa. The formation of the 1st South African Division(1st SA Div) during 1940, and the subsequent deployment of South African troops to the East African theatre, afforded the UDF the opportunity to test its military capabilities under operational conditions against the Italian threat in Ethiopia (then Abyssinia) and Somalia (then Italian Somaliland). It had been 21 years since the Union of South Africa was last in a state of war, and the UDF’s first battle in East Africa is a prime tool by which to measure concepts such as force design, military innovation and the operational employment of forces, to name but a few. The Battle of El Wak was not only the UDF’s initial battle in the East African campaign, but also South Africa’s first battle during the Second World War. By drawing from primary archival material and secondary sources, the article concludes that the Battle of El Wak had a definite impact on the entire South African campaign in East Africa.
Keywords: Second World War; East Africa; Union Defence Force; 1st South African Division; George Brink; El Wak